2021
DOI: 10.3390/rs13245172
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Step Method for Estimating Suspended Particle Size Based on In Situ Comprehensive Observations in the Pearl River Estuary in China

Abstract: The suspended particle size has great impacts on marine biology environments and biogeochemical processes, such as the settling rates of particles and sunlight transmission in marine water. However, the spatial–temporal variations in particle sizes in coastal waters are rarely reported due to the paucity of appropriate observations and the limitations of particle size retrieval methods, especially in areas with complex optical properties. This study proposed a remote sensing-based method for estimating the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The particle scattering (b p (λ), in m −1 ) was calculated as c pg (λ) minus a pg (λ) [33]. The backscattering measurements were conducted using the BB9 instrument with nine bands [21], and the particle backscattering coefficient (b bp (λ), in m −1 ) was obtained after the correction on raw BB9 data following the BB9 protocol [34]. b p (λ) and b bp (λ) were resampled at 5 m-depth intervals by averaging the data within a 0.5 m depth up and down, to match with the PSD and SPM datasets.…”
Section: Optical Properties Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The particle scattering (b p (λ), in m −1 ) was calculated as c pg (λ) minus a pg (λ) [33]. The backscattering measurements were conducted using the BB9 instrument with nine bands [21], and the particle backscattering coefficient (b bp (λ), in m −1 ) was obtained after the correction on raw BB9 data following the BB9 protocol [34]. b p (λ) and b bp (λ) were resampled at 5 m-depth intervals by averaging the data within a 0.5 m depth up and down, to match with the PSD and SPM datasets.…”
Section: Optical Properties Measurementsmentioning
confidence: 99%
“…The V(D) for each size bin was calculated using the random shape model in this study, and the total volume concentration (VC) within the measured size range could be derived by summing the V(D) of each size bin. It should be noted that the VC was calculated by summing the V(D) within the size bin of 4-33 (i.e., size range of 2.05-297 µm), as studies have shown that the data were not stable for the initial and final bins [21,38]. The particle number concentration N(D), which could be regarded as the number of spherical particles with the same diameter for each size bin, was derived by dividing V(D) by the volume of a sphere of the same diameter (Equation ( 1)).…”
Section: Psd Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations